Schizoanalytic Cartographies: On Maps and Models of Capitalism - Barker, Jason (Filozofski vestnik, 2017)
What potentials exist for representing capitalism as such? The question is posed in relation to the idea of cognitive mapping, as explored in Toscano and Kinkle’s Cartographies of the Absolute, before considering the abstract potentials of computing and Turing machines to this end, where capitalism might be modelled algorithmically.